Menilai Pemulihan Ekologis: Analisis Ekonomi Lingkungan terhadap Remediasi Tanah Terkontaminasi Minyak di Hutan Hujan Tropis - Lubis, Abdillah; Bahruddin; Suwondo; Efriyeldi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The hydrocarbon contamination affects approximately 5.9 ha of soil in Sultan Syarif Hasyim Grand Forest Park (Tahura SSH), a tropical rainforest in Riau Province, Indonesia. This study aims to determine the costs required to rehabilitate petroleum-contaminated soil and evaluate the economic significance of ecological restoration in a 5.9 ha area designated in Tahura SSH. This study provides a novel economic framework for assessing ecological damage and guiding recovery in a hydrocarbon-impacted area, integrating the Replacement Cost Method (RCM) through restoration cost calculations and the Resource Equivalence Analysis (REA) to assess and compensate for environmental damage-related losses. The study results show that the three main remediation technologies selected, bioventing, bioaugmentation & biostimulation, and ex-situ landfarming, were used to remediate oil-contaminated soil in Tahura SSH. The highest remediation costs are exsitu landfarming, followed by bioaugmentation and biostimulation, and then bioventing. The ex-situ land farming method incurred the highest remediation costs. Nevertheless, it causes ecological harm in the SSH Tahura Area. REA determined that the area required to replace oil-contaminated land should be twice the baseline from 5.9 ha to 12.8 ha. Furthermore, the compensation paid by REA for environmental damage exceeded the initial assessment by 116.1% compared to using the Replacement Cost Method (Bioaugmentation & Biostimulation, Bioventing, and Ex-Situ Landfarming). This study offers stakeholders guidance on determining a fair environmental value for oil-contaminated soil. Future studies